Qualidade de vida e sobrecarga de trabalho em cuidadores de idosos em seguimento ambulatorial - Oliveira, Déborah Cristina de; Carvalho, Gisele Souza Fontanini de; Stella, Florindo [UNESP]; Higa, Celina Matiko Hori; D'Elboux, Maria José (FapUNIFESP (SciELO), 2011)
We evaluated the quality of life related to health and work overloads among 126 caregivers to patients at two geriatric outpatient clinics of a university hospital, as well as the association between overloads and demographic and clinical variables, using an exploratory, descriptive, cross sectional and quantitative approach. The Zarit Burden Interview, a socio-demographic and clinical characterization instrument, was used to assess perceived workloads and the Medical Outcomes Study Short-Form Health Survey (SF-36) was used to assess quality of life related of health. Descriptive, comparative, correlative, and multivariate data analyses were carried out. There was significant difference between two outpatient caregiver workloads; all socio-demographic aspects and variables related to care were associated to worsening at least one dimension of the SF-36; frequent illnesses among caregivers were related to a worsening of their quality of life related to health, demonstrating the wear experienced by caregivers to the elderly in these health care units.
Quality of life and work overload among elderly outpatient caregivers
Keywords: Aged; Caregivers; Quality of life